Expression of LINE-1 retrotransposon in early human spontaneous abortion tissues. Issue 49 (9th December 2022) - Lou, Chao; Qiang, Rong; Wu, Hanzhi; Zhang, Liping; Li, Wei; Jia, Ting; Liu, Xing
Abstract : Background: The aim of this study is to investigate a new mechanism that may affect spontaneous abortions (SA): Can long interspersed nuclear element-1 (LINE-1) insertions in embryo cells lead to early SA? Methods: The method involves prospective study on new mechanism of human early SA. Twenty SA tissues and 10 induced abortion (IA) tissues were utilized for this experiment. Western Blot, Immunohistochemistry (IHC), and reverse transcription-polymerase chain reaction were used to analyze different LINE-1 proteins and mRNA expression between early SA tissues and early IA tissues. SPSS software version 21.0 was used for statistical analysis. Results: Western Blot demonstrated that the LINE-1 protein expression in SA tissues (Mean: 60.2%) is higher than in IA tissues (Mean: 30.3%) in 91% of the compared samples. reverse transcription-polymerase chain reaction showed that LINE-1 mRNA expression in SA tissues (Mean: 64.2%) is higher than in IA tissues (Mean: 29.2%) in 6 primer pairs in 89% of the compared samples. IHC showed that the LINE-1 protein expression in SA tissues (Mean: 59.2%) is higher than in IA tissues (Mean: 28.8%) in 83% of the compared samples. Conclusions: Expression of LINE-1 in early SA tissues is higher than in IA tissues, LINE-1 may lead to early SA and LINE-1 plays a role in early SA, this shows that a new mechanism may be involved in SA.